A comparative study on phenomenon and deep belief network models for hot deformation behavior of an Al–Zn–Mg–Cu alloy - Lin, Y. C.; Liang, Ying-Jie; Chen, Ming-Song; Chen, Xiao-Min (Applied physics. A, Materials science & processing, 2017)
The high temperature deformation behavior of an Al–Zn–Mg–Cu alloy is studied by isothermal compression tests at the temperature range of 573–723 K and strain rate range of 0.001–0.1 s −1 . Considering the coupled influences of deformation temperature, strain, and strain rate on hot deformation behavior, a deep belief network (DBN) model, as well as a phenomenological constitutive model, is developed for the studied alloy. In order to validate the developed models, the average absolute relative error and correlation coefficient are evaluated between the measured and predicted true stresses. The results show that the developed DBN model has the better predictability for the high temperature deformation behavior of the studied Al–Zn–Mg–Cu alloy. Moreover, the average absolute relative error and correlation coefficient of DBN model are 0.57% and 0.9997, respectively. In addition, the developed DBN model can be effectively applied in the intelligent manufacturing, such as intelligent isothermal die forging technology.